Holocene Pollen Records and Peatland Development, Northeastern Manitoba - Dredge, Lynda; Mott, Robert (Géographie physique et Quaternaire)

(untitled) (Les Presses de l'Université de Montréal, 2003)
AbstractPeatlands cover extensive parts of northeastern Manitoba that have low relief and impermeable substrates, with peat thicknesses varying between 25 and 400 cm. Peat reserves average 1.5 x 106 m3/km2. Fens, forested plateau bogs, and polygonal plateau bogs are the prevalent peatland types. The thickest peat deposits consist of Sphagnum bogs that developed on glaciolacustrine or marine silt. Thinner deposits are composed of fen peat, or bog peat developed on sandy till. There is a positive relationship between peat thickness and time since postglacial emergence of the land. Also, recently emerged areas are dominated by fen peat, whereas bog peat is more prevalent on older surfaces. Pollen analysis of peat cores show that spruce trees have been abundant in the region south of Churchill for the past 6300 years. Local changes in peat type and accumulation rate occurred as bog and fen habitats changed, probably in response to changes in water table induced by aggradation and degradation of permafrost. Other taxa typical of boreal forest occupied suitable habitats similar to today, with bog and fen habitats increasing as paludification continued through time.